SUPERVISI PENDIDIKAN SEBAGAI INSTRUMEN PENINGKATAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Dwi Aryanti (Jurnal Dinamika Pendidikan Islam, 2026)
Educational supervision is one of the strategic instruments in improving the quality of learning, particularly in Islamic Religious Education (PAI) subjects. The background of this study is based on the still low quality of PAI learning in a number of schools due to weak supervision by school principals and educational supervisors. The purpose of this study is to analyze the role of educational supervision as an instrument for improving the quality of PAI learning. The method used is descriptive qualitative with in-depth interview techniques, observation, and documentation study. The results show that supervision carried out in a planned, systematic, and sustainable manner can significantly improve the competence of PAI teachers. Findings also indicate that the clinical supervision approach is more effective than conventional supervision. It is concluded that quality educational supervision is the main key in achieving quality standards for PAI learning.